(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
From the field of interarts, this article reveals the poetic and artistic creation process of the photo-performance Watu conta contos. Through the philosophy of the imaginary (Bachelard, 2018; Durand, 1993; Ferreira-Santos; Almeida, 2020), the poetics of space (Bachelard, 2003; Certeau, 2025), and indigenous worldviews on orality/writing (Kopenawa, 2010; Krenak, 2020a, 2020b; Jecupé, 2023), the investigation aimed to promote new images and dialogues for the landscape of the Watu River, located in the municipality of Colatina-ES. To this end, the writing undertaken presents the work’s setting, the creative process of the photo-performance, and the captured images.